The darkest microbiome—a post‐human biosphere. Issue 1 (29th November 2021) - Timmis, Kenneth; Hallsworth, John E.
Summary: Microbial technology is exceptional among human activities and endeavours in its range of applications that benefit humanity, even exceeding those of chemistry. What is more, microbial technologists are among the most creative scientists, and the scope of the field continuously expands as new ideas and applications emerge. Notwithstanding this diversity of applications, given the dire predictions for the fate of the surface biosphere as a result of current trajectories of global warming, the future of microbial biotechnology research must have a single purpose, namely to help secure the future of life on Earth. Everything else will, by comparison, be irrelevant. Crucially, microbes themselves play pivotal roles in climate (Cavicchioli et al ., Nature Revs Microbiol 17 : 569–586, 2019). To enable realization of their full potential in humanity's effort to survive, development of new and transformative global warming‐relevant technologies must become the lynchpin of microbial biotechnology research and development. As a consequence, microbial biotechnologists must consider constraining their usual degree of freedom, and re‐orienting their focus towards planetary‐biosphere exigences. And they must actively seek alliances and synergies with others to get the job done as fast as humanly possible; they need to enthusiastically embrace and join the global effort, subordinating where necessary individual aspirations to the common good (the amazing speed with which new COVID‐19 diagnostics and vaccines were developed and implemented demonstrates what is possible given creativity, singleness of purpose and funding). In terms of priorities, some will be obvious, others less so, with some only becoming revealed after dedicated effort yields new insights/opens new vistas. We therefore refrain from developing a priority list here. Rather, we consider what is likely to happen to the Earth's biosphere if we (and the rest of humanity) fail to rescue it. We do so with the aim of galvanizing the formulation and implementation of strategic and financial science policy decisions that will maximally stimulate the development of relevant new microbial technologies, and maximally exploit available technologies, to repair existing environmental damage and mitigate against future deterioration. Abstract : Clearly, to avoid, or at least delay, a scenario like that depicted above, humanity must immediately institute radical changes that drastically reduce greenhouse gas emissions and other planet‐destroying activities, and single‐mindedly seek to develop and exploit new technologies to repair existing damage. Moreover, we must enter into more cooperative relationships with microbes and other life‐forms and, with them, devise new and transformative technologies to solve or mitigate current and future global, regional and local environmental problems. This will necessitate changes in mindsets (e.g. see Timmis and Ramos, Microb Biotechnol 14 : 769–797, 2021). The next 15 years of microbial biotechnology must largely be devoted to the discovery and development of new microbial technologies that contribute significantly towards sustainability. Hopefully, during this time, humankind, with microbial assistance, will reorient its developmental trajectory to one that is consistent with the survival of Earth's surface biosphere.